Habitual physical activity is associated with circulating irisin in healthy controls but not in subjects with diabetes mellitus type 2. (17th July 2015) - Al‐Daghri, Nasser M.; Alokail, Majed S.; Rahman, Shakilur; Amer, Osama E.; Al‐Attas, Omar S.; Alfawaz, Hanan; Tripathi, Gyanendra; Sabico, Shaun; Chrousos, George P.; McTernan, Philip G.; Piya, Milan K.
Abstract Background Irisin, a novel myokine, has been shown to increase following vigorous exercise, with studies suggesting that it mediates some of the beneficial effects of exercise. Irisin might play a role in 'browning' of white adipocytes, thus increasing energy expenditure. The role of irisin in exercise and energy expenditure in subjects with diabetes mellitus type 2 (DMT2) remains largely unknown. We aimed to investigate the association between circulating irisin and habitual physical activity in subjects with and without DMT2. Material and methods In this cross‐sectional study, 164 Saudi adults: 81 non‐DMT2 controls [age: (mean ± SD) 51·6 ± 10·9; BMI: 29·6 ± 4·3 kg/m2] and 83 DMT2 subjects [age: 54·3 ± 10·3 year; BMI: 29·4 ± 4·7 kg/m2] were studied. Anthropometric and fasting serum biochemical data were collected. Circulating irisin was measured using an enzyme‐linked immunosorbent assay (ELISA). Frequency intensity time (FIT) index was used to assess the level of habitual physical activity. Results We observed significantly higher levels of irisin in DMT2 subjects than in controls (P < 0·001). FIT index was positively associated (r = 0·20, P = 0·03) with circulating irisin in controls only. Additionally, irisin levels were significantly higher in tertile 3 (0·75 ± 0·07 μg/mL) than tertile 1 (0·49 ± 0·06 μg/mL) of the FIT index in healthy controls, whilst no such relation with physical activity was observed in DMT2 subjects. Conclusion This cross‐sectional study has shown a weak association of irisin with physical activity levels in healthy controls but not in DMT2 subjects, suggesting the possibility of discordant regulation in the condition of DMT2.